2004
DOI: 10.1148/radiol.2303021345
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Gland Hematomas in Trauma Patients

Abstract: Adrenal hematoma was detected in 51 (1.9%) of 2,692 trauma patients who underwent CT, or 0.8% of all patients (n = 6,808) entered in the trauma registry. Compared with the other trauma patients, the patients with adrenal hematomas had severe injuries associated with higher mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 13 publications
9
62
0
1
Order By: Relevance
“…ϾAdrenal gland injuries are rare in blunt abdominal trauma, and most are associated with great injury severity (1,2). Due to the unique adrenal anatomy and the trauma mechanism, adrenal injury is typically unilateral and right-sided (1)(2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…ϾAdrenal gland injuries are rare in blunt abdominal trauma, and most are associated with great injury severity (1,2). Due to the unique adrenal anatomy and the trauma mechanism, adrenal injury is typically unilateral and right-sided (1)(2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…1). A study by Rana et al showed adrenal hematomas to be round or ovoid with a mean diameter of 2.8 cm and attenuation of 52 HU on contrast-enhanced CT [8]. Over time, the hematoma typically decreases in size and attenuation and may completely resolve.…”
Section: Traumamentioning
confidence: 99%
“…The diagnosis of ADGI has increased in recent years due to the application of multidetector Computed tomography (CT) scanning in the trauma setting and its accuracy in differentiation of adrenal trauma from other masses [10]. CT scan findings which are suggestive of ADGI are round or oval hematoma expanding the adrenal gland, irregular hematoma obliterating the gland, and uniform adrenal enlargement [8].…”
Section: Introductionmentioning
confidence: 99%